A squaraine-based dipicolylamine derivative acting as a turn-on mercury(ii) fluorescent probe in water. (9th April 2020) - Esteves, Catarina V.; Costa, Judite; Bernard, Hélène; Tripier, Raphaël; Delgado, Rita
Abstract : A squaraine-based ligand, sbdpa, has been synthesized, and the behaviour of its metal complexes was investigated. It was found that it acts as a Hg 2+ chemosensor in aqueous solution. Abstract : A symmetrical squaraine-based ligand, sbdpa, bearing two dipicolylamine (dpa) units, was synthesized for the first time, using an environment friendly procedure, such as one-pot and solvent-free reaction. The sbdpa ligand was found to have a small blue-green emission, in aqueous solution, due to a photoinduced electron transfer (PET) mechanism. Metal complexes of sbdpa with a large panel of cations, Na +, K +, Ag +, Mg 2+, Ca 2+, Ba 2+, Mn 2+, Fe 2+, Co 2+, Ni 2+, Cu 2+, Zn 2+, Cd 2+, Hg 2+, and Pb 2+, were prepared in aqueous buffered solution and screened, in search of a selective response for one of them. A turn-on fluorescence response was then found only for Hg 2+, as a consequence of a chelation-enhanced fluorescence (CHEF) effect that disrupts the PET mechanism in sbdpa . Subsequently, the complexation behaviour of Hg 2+ with sbdpa was investigated in aqueous solution by potentiometric titrations and other spectroscopic techniques. The acid–base reactions of the ligand were also studied by potentiometry, as well as by 1 H-NMR and UV-vis titrations. For comparison purposes, the complexation of two other divalent cations, Cu 2+ and Zn 2+, was also assessed by potentiometry. Additionally, results are compared with dpa all along the study. Both mono- and dinuclear complexes of sbdpa were found for the three metal cations studied the mercury(ii ) complex having the largest thermodynamic stability. These findings support a stronger uptake of Hg 2+ cation by sbdpa, possibly involving at least one oxygen atom from the squaraine moiety on its coordination sphere.